Pemodelan Simulasi Tabung Penyerap Energi Crash Box Sebagai Teknologi Keselamatan Pasif Berbasis Software FEM (Finite Elemen Methode) - Willy Wirawan; Adya Aghastya; Septiana Widi Astuti; Natriya Faisal Rachman; Suprapto Suprapto; Yustina Titin Purwantiningsih (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
A crash box is one of the absolute safeties in transportation that functions as a means ofabsorbing impact energy to reduce injuries to drivers and passengers due to collisions or accidents. This study aims to determine the value of energy absorption and the resulting deformation pattern on the crash box in the form of a one-segment circular tube. The method in this study uses a quasiexperimental using finite element-based simulation software (finite element method). The variables in this study include a tube length of 300 mm with variations in the thickness of 1,5 mm and 3 mm and a tube diameter of 120 mm. A quasi-static collision test will be carried out with an impactor with a mass of 200 kg and a speed of 10 m/s. The simulation on the crash box is observed based on the value of energy absorption, reaction force, and the formed deformation pattern. The simulation results show that the highest energy absorption value is found in the 3 mm thick crash box of 790000 Joules. The reaction force of 230000 N. It can be seen that the deformation pattern formed tends to bend in the 1,5 mm thick crash box and forms a concertina pattern on the thick crash box is 3 mm..